Double-blinded, randomized tolerance study of a biologically enhanced Nanogel with endothelin-1 and bradykinin receptor antagonist peptides via intra-articular injection for osteoarthritis treatment in horses - Antoinette Terlinden; Sandrine Jacquet; Seng Manivong; Aurélie Cullier; Frédéric Cassé; Florence Legendre; Araceli Ac Garcia; Gaëlle Roullin; Florina Moldovan; Pierre Sirois; Xavier Banquy; Philippe Galéra; et al. (BMC Veterinary Research)
Abstract Background Osteoarthritis is a leading cause of pain and retirement in athletic horses. Hydro-expansive functionalized nanogels, acting as Drug Delivery Systems, constitute one of the current therapeutic prospects. These nanogels have the potential to combine mechanical benefits through polymers with the biological effect of prolonged release of bioactive molecules. The purpose of this double-blinded randomized tolerance study versus negative control was to evaluate the response of healthy joints to a single injection of the expected efficient dose (further referred to as the trial dose) and overdose of nanogels composed of chitosan and hyaluronic acid and featuring a type A endothelin receptor antagonist and a type B1 bradykinin receptor antagonist. The metacarpophalangeal joints of 8 healthy horses were randomly injected with 2.4 mL of functionalized nanogels and 2.4 mL of saline as control on the contralateral limb. Injections were repeated twice at one-week intervals, followed by injection of a triple dose of nanogel on week four. Clinical, ultrasonographic and synovial fluid cellular and biochemical follow-ups were performed up to three months following the first injection. Results No change in general clinical parameters, lameness or sensitivity to passive flexion of the fetlocks was noted. Mild to moderate synovitis was noted on the day following injection in the treated group, with a significant difference (p < 0.05) compared to the control group. It spontaneously resolved on day 3 following the injections and did not increase with repeated injections. Similar effects were noted after injection of the triple dose but lasted for a week. Synovial fluid markers of inflammation also showed a transient significant increase in the treated group one week after each injection, but no differences were detected at the end of the study. Conclusions Injections of the expected therapeutic dose of functionalized nanogel in healthy joints induced a mild transient inflammatory response in the joint. Three injections of the trial dose at one-week intervals and injection of thrice the trial dose induce a mildly greater inflammation without harmful effects on joints. Functionalized nanogels are well tolerated prospects for the treatment of osteoarthritis in horses. Their beneficial effects on arthritic joints have yet to be evaluated to determine their therapeutic potential.